The seven swords - Johnson-Shelton, Nils (Johnson-Shelton, Nils. Otherworld chronicles., 2013)
"Twelve-year-old Artie Kingfisher has only ten days to gather a team of knights to wield the mythical seven swords, or his mission to save the Otherworld and claim his throne as King Arthur will be lost"--Provided by publisher.